2020
DOI: 10.1007/s12529-020-09873-w
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Adversity and Sleep Disturbances: Longitudinal Results in Puerto Rican Children

Abstract: Background-Exposure to childhood adversities (CA) is associated with sleep disturbances; however, evidence has largely been drawn from cross-sectional data and has not addressed the relationship across developmental stages. Also, most studies have primarily focused on non Hispanic White cohorts with a dearth of longitudinal evidence about racial/ethnic minorities. We examined the longitudinal association between CA and sleep disturbances in Puerto Rican youth. Method-The Boricua YouthStudy is a longitudinal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 56 publications
0
18
0
1
Order By: Relevance
“… 73 Finally, in a recent longitudinal cohort study of 2491 children at 5–9 and 10–16 years old, having an accumulation of childhood adversities significantly associated with sleep disturbances in youth 10–16 years, but not in younger children. 74 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 73 Finally, in a recent longitudinal cohort study of 2491 children at 5–9 and 10–16 years old, having an accumulation of childhood adversities significantly associated with sleep disturbances in youth 10–16 years, but not in younger children. 74 …”
Section: Methodsmentioning
confidence: 99%
“… Infants with a secure pattern of attachment with mothers had lower number of night wakings over time. Sleep and Childhood Maltreatment April-Sanders et al (2021) 74 Longitudinal 2491 Range=5–9 and 10–16 years Age grouping: childhood and adolescence. N/A Parent and youth report; prevalence of sleep disturbances.…”
Section: Methodsmentioning
confidence: 99%
“…[ [30][31][32][33] Circadian rhythm disruption Often measured as disrupted circadian cortisol secretion or secondarily as clock gene expression. [34][35][36] Substance Misuse/Abuse/Addiction Smoking/Alcohol/Drugs [37,38] Additional Risky Behavior Early sex, multiple partners/early pregnancy [39] Chronic pain Both adolescent and adult onset; cortisol levels can be a biomarker.…”
Section: Conditions/attribute Details Referencesmentioning
confidence: 99%
“…Research has shown that the relationship between experiencing domestic violence between household members and subsequent depression may be improved by tackling sleep problems first [ 133 ]. Living with domestic violence may result in sleep deficiency that persists even after the abuse has ended [ 134 ]. Similarly, children who have experienced either physical and/or sexual abuse report more sleep deficiency issues than children who are not abused [ 135 , 136 ], and these effects on sleep are long-term [ 137 , 138 ].…”
Section: Nutrition Dietary Intake and Weightmentioning
confidence: 99%